2012
DOI: 10.1007/s00264-012-1634-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo comparisons of patellofemoral kinematics before and after ADVANCE® Medial-Pivot total knee arthroplasty

Abstract: Purpose ADVANCE® Medial-Pivot (MP) (Wright Medical Technology, Arlington, TN, USA) total knee arthroplasty (TKA) was developed to replicate normal tibiofemoral knee joint kinematics, allowing medial-pivot knee motion. The design concept of the prosthesis is unique; therefore, the influence on the patellofemoral knee joint remains unclear at present. The purpose of this study was to determine the in vivo patellofemoral kinematics with ADVANCE® MP TKA and compare them with the pre-operative conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…The MP motion can reduce the patellofemoral pressure, reproduce normal tibiofemoral kinematics, decrease risk of patellofemoral complications, such as anterior knee pain. [ 27 ] Anderson et al [ 10 ] reported patients undergoing surgery with MP prosthesis had significantly lower rates of patellofemoral complications compared with patients who underwent surgery with PS prosthesis, while Ishida et al [ 28 ] reported the influence of MP prosthesis on the clinical outcome of patellofemoral joint after TKA is still unclear. In our study, we only evaluated patellar tilt angle, and there was not any investigation of the clinical rating system and the other radiographic parameters for patellofemoral joint.…”
Section: Discussionmentioning
confidence: 99%
“…The MP motion can reduce the patellofemoral pressure, reproduce normal tibiofemoral kinematics, decrease risk of patellofemoral complications, such as anterior knee pain. [ 27 ] Anderson et al [ 10 ] reported patients undergoing surgery with MP prosthesis had significantly lower rates of patellofemoral complications compared with patients who underwent surgery with PS prosthesis, while Ishida et al [ 28 ] reported the influence of MP prosthesis on the clinical outcome of patellofemoral joint after TKA is still unclear. In our study, we only evaluated patellar tilt angle, and there was not any investigation of the clinical rating system and the other radiographic parameters for patellofemoral joint.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, medial pivoting knee motion has also been adopted in several knee replacement designs that are aimed to reproduce anatomic knee joint motion patterns (Chinzei et al, 2014; Ishida et al, 2012; Morra et al, 2008; Pritchett, 2011; Schmidt et al, 2003; Schmidt et al, 2014). However, our data showed that both the medial and lateral cartilage contacts are a convex femur to a convex tibia contact in sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term survival rate of prostheses is always the gold standard to measure the success or failure of knee replacement surgery. Previous studies suggested that MP prostheses can provide better articulating joints while reducing the contact stress load on the fixed surface, which should reduce the risk for loosening [20,21]. However, an increasing number of authors have confirmed that the wear of this type of joint is affected by many mechanical and biological factors, so the long-term life of the prosthesis cannot be measured by a single factor [22].…”
Section: Discussionmentioning
confidence: 99%